IEEE International Conference on Acoustics Speech and Signal Processing 2002
DOI: 10.1109/icassp.2002.5743726
|View full text |Cite
|
Sign up to set email alerts
|

The DYPSA algorithm for estimation of glottal closure instants in voiced speech

Abstract: We present the DYPSA algorithm for automatic and reliable estimation of glottal closure instants (GCIs) in voiced speech. Reliable GCI estimation is essential for closed-phase speech analysis, from which can be derived features of the vocal tract and, separately, the voice source. It has been shown that such features can be used with significant advantages in applications such as speaker recognition. DYPSA is automatic and operates using the speech signal alone without the need for an EGG or Laryngograph signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…In this paper, it was shown that the energy-weighted measures performed better than the other two measures. A dynamic programming projected phase-slope algorithm (DYPSA) for automatic estimation of glottal closure instants in voiced speech was presented in [22] and [23]. In this method, the candidates for GCI were obtained from the zero crossings of the phase-slope function derived from the energy-weighted group-delay, and were refined by employing a dynamic programming algorithm.…”
Section: B Review Of the Existing Methodsmentioning
confidence: 99%
“…In this paper, it was shown that the energy-weighted measures performed better than the other two measures. A dynamic programming projected phase-slope algorithm (DYPSA) for automatic estimation of glottal closure instants in voiced speech was presented in [22] and [23]. In this method, the candidates for GCI were obtained from the zero crossings of the phase-slope function derived from the energy-weighted group-delay, and were refined by employing a dynamic programming algorithm.…”
Section: B Review Of the Existing Methodsmentioning
confidence: 99%
“…Additionally, due to the propagation time between the EGG and the waveform, the reference GCIs and the detected GCIs are synchronized for each utterance by maximizing their correlation. Four methods are compared: the proposed method using MSP, the previously proposed method using a Glottal Shape estimate (GCIGS) [39], the DYPSA method [14] and another method based on Group-Delay (GD) [15], [18]. Figure 4 shows the evaluation results on three CMU Arctic databases [40].…”
Section: ) Evaluation Of Gci Estimatesmentioning
confidence: 99%
“…In terms of phase, the better the estimate of the model, the smaller the phase spectrum of the convolutive residual. This criterion has already been proposed to estimate Glottal Closure Instants (GCI) resulting in robust estimators [14], [15]. In these methods, assuming the source is a Dirac delta and the VTF is an all-pole filter, the phase spectrum of an LP residual is minimized.…”
Section: Introductionmentioning
confidence: 99%
“…The pitch deviation cost is a function of the current and previous two GCI candidates under consideration by the DP and is defined as (12) where the pitch deviation is (13) The cost increases nonlinearly with from 0.5 to 0.5, applying relatively small penalties for minor pitch changes based on an assumption of smooth variation in pitch over short segments of voiced speech. The rate of increase of cost with pitch deviation is controlled by and zero cost is obtained at (14) In our experiments, has been employed so as to obtain zero cost at pitch deviation of 25%.…”
Section: ) Pitch Deviation Costmentioning
confidence: 99%
“…We also briefly discuss approaches to estimate GOIs. An earlier version of the DYPSA algorithm was outlined in [13].…”
Section: Introductionmentioning
confidence: 99%